2005
DOI: 10.1002/ajmg.a.30643
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of chromosome 4q: Renal pathology of two siblings

Abstract: We report on two sibs with partial 4q trisomy: dup (4)(q35.2-q31.22) and their renal biopsy findings. Both of them show renal hypoplasia, although their chromosomal aberration lacks the minimal duplicated region 4q22-q23 and/or 4q25-q31.3, which had been shown to be associated with urogenital abnormalities and thumb malformations in previous reports. From the renal biopsy findings, the two sibs were diagnosed as oligonephronia. We summarize the 13 having published cases of duplication of chromosome 4q, and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
0
29
2
Order By: Relevance
“…To our knowledge, 17 studies have described the pure 4q duplication region covering the 4q22q32 region [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] 30,31 Contrary to the reports of these researchers, we did not observe thumb or renal abnormalities in our patients having a 4q22q32 duplication. To our knowledge, the present study is the first report of a pure and recurrent 4q duplication investigated with CGH microarray technology and microsatellite analysis.…”
Section: Discussioncontrasting
confidence: 93%
“…To our knowledge, 17 studies have described the pure 4q duplication region covering the 4q22q32 region [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] 30,31 Contrary to the reports of these researchers, we did not observe thumb or renal abnormalities in our patients having a 4q22q32 duplication. To our knowledge, the present study is the first report of a pure and recurrent 4q duplication investigated with CGH microarray technology and microsatellite analysis.…”
Section: Discussioncontrasting
confidence: 93%
“…However, preaxial polydactyly in the patients by Genčik et al [1982] and Otsuka et al [2005] who had trisomy for more distal segments of 4q contradicts this hypothesis. The last patient had ''pure'' trisomy 4q, and spectral karyotyping was used to determine the triplicated segment.…”
mentioning
confidence: 67%
“…The controversy between hypothesis of Battaglia et al [2005] and observations by Genčik et al [1982] and Otsuka et al [2005] may be explained in two different ways: a) preaxial polydactyly and underdevelopment of thumbs may be caused by duplications of two different segments within 4q; b) localization of the breakpoints at least in one of the cases, crucial for the issue, was not precise.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…However, Battaglia et al [2005] postulated genes important in the development of the acrorenal field were likely present in 4q25 ] q28. In addition, after summarizing 13 published cases of simple partial trisomy 4q, Otsuka et al [2005] suggested that renal hypoplasia may be female-prone, and may have a close relationship with duplication of 4q33 ] q34. This segment is also duplicated in our patient, however, she does not suffer from renal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%